Global analysis of satellite tracking data shows that adult green turtles are significantly aggregated in Marine Protected Areas - Scott, Rebecca (2013)
Aim Tracking technologies are often proposed as a method to elucidate the complex migratory life histories of migratory marine vertebrates, allowing spatially explicit threats to be identified and mitigated. We conducted a global analysis of foraging areas of adult green turtles (Cheloniamydas) subject to satellite tracking (n = 145) and the conservation designation of these areas according to International Union for Conservation of Nature criteria. Location The green turtle has a largely circumtropical distribution, with adults migrating up to thousands of kilometres between nesting beaches and foraging areas, typically in neritic seagrass or algal beds. Methods We undertook an assessment of satellite tracking projects that followed the movements of green turtles in tropical and subtropical habitats. This approach was facilitated by the use of the Satellite Tracking and Analysis Tool (http:// www.seaturtle.org) and the integration of publicly available data on Marine Protected Areas (MPAs). Results We show that turtles aggregate in designated MPAs far more than would be expected by chance when considered globally (35% of all turtles were located within MPAs) or separately by ocean basin (Atlantic 67%, Indian 34%,Mediterranean 19%, Pacific 16%). Furthermore,we show that the size, level of protection and time of establishment of MPAs affects the likelihood of MPAs containing foraging turtles, highlighting the importance of large, well-established reserves. Main conclusions Our findings constitute compelling evidence of the worldwide effectiveness of extant MPAs in circumscribing important foraging habitats for a marine megavertebrate.